The lover - Duras, Marguerite; Bray, Barbara (London ; New York : Harper Perennial, 2006)
A sensational international bestseller, and winner of Frances' coveted Prix Goncourt, `The Lover' is an unforgettable portrayal of the incandescent relationship between two lovers, and of the hate that slowly tears the girl's family apart.
This translation originally published: 1985.
ENH
Karim International
Keywords: Teenage girls -- Indochina -- Fiction; Man-woman relationships -- Indochina -- Fiction; Indochina -- Fiction